Cesty k založení časopisu Lidé města / Urban People: Osobní vzpomínky k 20. výročí časopisu - Moravcová, Mirjam (Lidé města, 2019)
The Lidé města Journal has successfully concluded its twentieth year of publication; the first ten years were summarised bibliographically at the end of the tenth year (10, 2008, 3), and the second decade at the end of the twentieth year (20, 2018, 3). The twentieth anniversary of the journal inspired its founder and long-term Editor-in-Chief, Mirjam Moravcová, to write down her memories about how this periodical came about, about its institutional background, and about the figures that had a hand in the journal’s conception and publication throughout the years.